A clinicopathological evaluation on thrombocytosis in correlation with platelet indices in a tertiary care hospital: a retrospective study - K. S., Muhammed Safwan; K. M., Prajna; Ullas, Chaithanya (International Journal of Research in Medical Sciences, 2024)
Background: Thrombocytosis refers to platelet count >450×109/l in the peripheral blood. It is classified into primary and secondary forms. An increased platelet count has emerged as a significant clinical issue for the differential diagnosis of numerous physiological and pathological conditions. This study was done to evaluate the clinical study on patients with thrombocytosis in correlation with platelet indices. Methods: This was a retrospective study which included 105 subjects. EDTA samples were collected from thrombocytosis patients for the estimations of platelet indices. The severity of thrombocytosis was grouped as Mild, Moderate, Severe and Extreme. The results were analysed using SPSS Software. Results: Commonly encountered etiological findings were secondary thrombocytosis (97.14%). Correlation in between the various platelet indices, the PCT was positively correlated with PLT count as well as MPV, and the PDW was positively correlated with MPV as well as PCT. According to the severity of thrombocytosis, significant difference was observed with PLT count and PCT, no statistical significance was observed in MPV or PDW. Conclusions: The study found that secondary thrombocytosis was the main etiological factor for thrombocytosis, which is primarily driven by respiratory tract infections, gastrointestinal tract infections, urinary tract infections, and other infections (bacterial infections and viral infections). Platelet indices such as PLT count and PCT showed statistical significance with the severity of thrombocytosis and no statistical significance in MPV and PDW.